Mechanism of the Decomposition of Aqueous Hydrogen Peroxide over Heterogeneous TiSBA15 and TS-1 Selective Oxidation Catalysts: Insights from Spectroscopic and Density Functional Theory Studies - Yoon, Chang Won; Hirsekorn, Kurt F.; Neidig, Michael L.; Yang, Xinzheng; Tilley, T. Don (AMER CHEMICAL SOC, 2011)
The Ti-based heterogeneous catalysts TiSBA15, Bu(cap)TiSBA15, TS-1, and [Ti,Al]-MFI were investigated with respect to controlling factors for the competitive decomposition of aqueous H2O2 during selective catalytic oxidations. DRUV vis spectroscopy revealed that the titanium species in these materials exist mainly in isolated, tetrahedral coordination environments. The observed rates of H2O2 decomposition at 65 degrees C in acetonitrile decreased in the following order: Bu(cap)TiSBA15 > TiSBA15 and TS-1 > [Ti,Al]-MFI. The decompositions of H2O2 were also monitored in the presence of inorganic additives and Bronsted acids and bases, in benzene/aqueous biphasic solutions. Significant retardation of the decomposition rates with the KH2PO4 additive was found with TiSBA15, which suggests that the. KH2PO4 stabilizer may be useful for optimization of hydrogen peroxide efficiency in catalytic oxidations. DRUV-vis spectroscopy was employed to identify possible catalytically active intermediates, proposed to be Ti(IV) (OOH) species that are produced upon reaction of the Ti-based materials and H2O2. Density Functional Theory (DFT) studies starting from a molecular model, (HO)Ti[OSi(OH)(3)](3), suggest that three Ti(IV) (OOH) intermediates are in equilibrium,rand the formation of Ti-O-circle and HOO circle radical species may be involved in the H2O2 decomposition. In addition, the potential role of KH2PO4 in the H2O2 decomposition process, as a proton acceptor in a [Ti(OO)(HOP(O)(OH)(2))] complex, has been investigated.
Keywords: TITANIUM SILICALITE; MOLECULAR PRECURSOR; SURFACE MODIFICATION; ALKENE EPOXIDATION; OLEFIN EPOXIDATION; CRYSTAL-STRUCTURE; OXYGEN-TRANSFER; ANHYDRIDE FORM; TI; REACTIVITY